2019
DOI: 10.3892/etm.2019.8117
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the activity of certain genes involved in tumor cell metabolism in the presence of the cytotoxic peptides defensin and cathelicidin LL37

Abstract: It is common knowledge that some natural antimicrobial peptides also have a tumoricidal effect. We have shown that the peptides defensin and cathelicidin LL37 have cytostatic effects on human tumor cell lines HT29 (colorectal carcinoma) and A549 (alveolar carcinoma). In order to determine the modulating mechanism of these peptides we assessed the gene expression of the AKT, HIF-1α, XBP, NRF2, PERK, CHOP, BCL2, IRE1α and PI3K molecular targets involved in the survival, growth, proliferation and apoptosis pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Ștefanache et al (11) have demonstrated in previous studies that that the peptides, defensin and cathelicidin LL37, exert cytostatic effects on the following human tumor cell lines: HT29 (colorectal adenocarcinoma) and A549 (alveolar carcinoma). In their original article, entitled ‘Modulation of the activity of certain genes involved in tumor cell metabolism in the presence of the cytotoxic peptides defensin and cathelicidin LL37’, they assessed the gene expression of the AKT, HIF-1α, XBP, NRF2, PERK, CHOP, BCL2, IRE1α and PI3K molecular targets involved in the survival, growth, proliferation and apoptosis pathways of tumor cells in the presence or absence of the peptides examined.…”
mentioning
confidence: 99%
“…Ștefanache et al (11) have demonstrated in previous studies that that the peptides, defensin and cathelicidin LL37, exert cytostatic effects on the following human tumor cell lines: HT29 (colorectal adenocarcinoma) and A549 (alveolar carcinoma). In their original article, entitled ‘Modulation of the activity of certain genes involved in tumor cell metabolism in the presence of the cytotoxic peptides defensin and cathelicidin LL37’, they assessed the gene expression of the AKT, HIF-1α, XBP, NRF2, PERK, CHOP, BCL2, IRE1α and PI3K molecular targets involved in the survival, growth, proliferation and apoptosis pathways of tumor cells in the presence or absence of the peptides examined.…”
mentioning
confidence: 99%